Lessons from the American Federal-State unemployment insurance system for a European unemployment benefits system - Christopher J. O'Leary; Burt S. Barnow (W.E. Upjohn Institute for Employment Research, 2016)
The federal-state system of unemployment insurance (UI) in the United States was established by the Social Security Act of 1935 during the Great Depression. Under the program, states provide temporary partial wage replacement to involuntarily unemployed workers with significant labor force attachment. The federal government induced states to establish UI programs through two means: 1) a uniform federal tax imposed on employer payrolls, with a 90 percent reduction granted in states operating approved UI programs, and 2) grants to states to administer their programs. The system has evolved into a collection of separate state programs adapted to different regional, economic, and cultural contexts that all meet the same standards. This paper reviews state practices concerning applicant eligibility, benefit generosity, and benefit financing, with the aim of revealing lessons for a possible European unemployment benefit system (EUBS). We examine areas of federal leadership, explicit federal-state cooperation, and state innovation. While the U.S. system offers some good ideas for setting up an EUBS, there are also lessons in some shortcomings of the U.S. experience. We identify areas of risk for individual and institutional moral hazard in a multi-tiered UI system, and give examples of monitoring methods and incentives to ameliorate such risks. We suggest approaches for gradual system development, encouraging lower-tier behavior, benefit financing, and responses to regional and system-wide crises.
Keywords: J65; H81; H87; 330; unemployment insurance; European unemployment benefit system; multi-tiered system; moral hazard; incentives; public finance